Review on bubble formation, rise and break-up in a gas-liquid system - Kulkarni, Amol A.; Joshi, Jyeshtharaj B. (Industrial & Engineering Chemistry Research, 2005)
The formation of gas bubbles and their subsequent rise due to buoyancy are very important fundamental phenomena that contribute significantly to the hydrodynamics in gas−liquid reactors. The rise of a bubble in dispersion can be associated with possible coalescence and dispersion followed by its disengagement from the system. The phenomenon of bubble formation decides the primitive bubble size in the system (which latter attains an equilibrium size), whereas the rise velocity decides the characteristic contact time between the phases which governs the interfacial transport phenomena as well as mixing. In view of their importance, we herein present a comprehensive review of bubble formation and bubble rise velocity in gas−liquid systems. The emphasis of this review is to illustrate the present status of the subjects under consideration and to highlight the possible future directions for further understanding of the subject. The bubble formation at a single submerged orifice and on multipoint sieve trays in Newtonian as well as non-Newtonian stagnant and flowing liquids is discussed in detail, which includes its mechanism as well as the effect of several system and operating parameters on the bubble size. The comparison of results has shown that the formulation of Gaddis and Vogelpohl22 is the most suitable for the estimation of bubble size in stagnant liquids. The special cases, such as bubble formation in reduced gravity conditions and weeping and in flowing liquids, are discussed in detail. The section on the rise of a gas bubble in liquid covers the various parameters governing bubble rise and their effect on the rise velocity. A comprehensive comparison of the various formulations is made by validating the predictions with experimental data for Newtonian as well as non-Newtonian liquids, published over last several decades. The results highlight that for the estimation of rise velocity in (i) pure Newtonian liquids, (ii) contaminated Newtonian liquids, and (iii) non-Newtonian liquids, the formulation based on the wave theory by Mendelson,190 Nguyen's formulation,155 and the formulation by Rodrigues,153 (last two, based on the dimensional analysis), respectively are the most suitable. The motion of bubbles in non-Newtonian liquids and the reason behind the discontinuity in the velocity are also discussed in detail. The bubble rise is also analyzed in terms of the drag coefficient for different system parameters and bubble sizes.

Data-driven dynamic modeling and control of a surface aeration system - Gandhi, Ankit B.; Joshi, Jyeshtharaj B.; Jayaraman, Valadi K.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2007)
In this study we have developed a support vector regression (SVR) based data-driven model for predicting two important design parameters of surface aerators, namely, the volumetric mass transfer coefficient (k(L)(a) under bar) and fractional gas hold-up (epsilon(G)). The dynamical state of the surface aerator system was captured by acquiring pressure fluctuation signals (PFSs) at various design and operating conditions. The most informative features from PFS were extracted using the chaos analysis technique, which includes estimation of Lyapunov exponent, correlation dimensions, and Kolmogorov entropy. At similar conditions the values of k(L)(a) under bar and epsilon(G) were also measured. Two different SVR models for predicting the volumetric mass transfer coefficient (k(L)(a) under bar) and overall gas hold-up (epsilon(G)) as a function of chaotic invariants, design parameters, and operating parameters were developed showing test accuracies of 98.8% and 97.1%, respectively. Such SVM based models for the surface aerator can be potentially useful on a commercial scale for online monitoring and control of desired process output variables.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Development of support vector regression (SVR)-based correlation for prediction of overall gas hold-up in bubble column reactors for various gas-liquid systems - Gandhi, Ankit B.; Joshi, Jyeshtharaj B.; Jayaraman, Valadi K.; Kulkarni, Bhaskar D. (Chemical Engineering Science, 2007)
The objective of this study was to develop a unified data-driven correlation for the overall gas hold-up for various gas-liquid systems using support vector regression (SVR)-based modeling technique. Over the years, researchers have amply quantified the hydrodynamics of bubble column reactors in terms of the overall gas hold-up. In this work, about 1810 experimental points were collected from 40 open sources spanning the years 1965-2007. The model for overall gas hold-up was established as a function of several parameters which include superficial gas velocity, superficial liquid velocity, gas density, molecular weight of gas, sparger type, sparger hole diameter, number of sparger holes, liquid viscosity, liquid density, liquid surface tension, operating temperature, operating pressure and column diameter of the gas-liquid system. For understanding the hold-up behavior, the data used for training the model was grouped into various gas-liquid systems viz., air-water, gas-aqueous viscous liquids, gas-organic liquids, gas-aqueous electrolyte solutions and gas-liquid systems operated over a wide range of pressure. A generalized model established using SVR was evaluated for its performance for various gas-liquid systems. Statistical analysis showed that the proposed generalized SVR-based correlation for overall gas hold-up has prediction accuracy of 97% with average absolute relative error (% AARE) of 12.11%. A comparison of this correlation with the selected system specific correlations in the literature showed that the developed SVR-based correlation significantly gives enhanced prediction of overall gas hold-up. (C) 2007 Published by Elsevier Ltd.
8th International Conference on Gas-Liquid and Gas-Liquid-Solid Reactor Engineering, Indian Inst Technol Delhi, New Delhi, INDIA, DEC 16-19, 2007
Keywords: bubble column reactor; overall gas hold-up; support vector regression

Identification and characterization of flow structures in chemical process equipment using multiresolution techniques - Deshpande, Sagar S.; Joshi, Jyeshtharaj B.; Kumar, V. Ravi; Kulkarni, B. D. (Chemical Engineering Science, 2008)
Planar information of velocity from 2D particle image velocimetry (PIV) and large eddy simulation (LES) data have been studied using multiresolution wavelet transform (WT) formalisms, i.e., discrete and continuous WT. Identification of dominant energy containing structures with their characterization in terms of fractal spectra have been carried out for industrially important equipment exhibiting turbulent behavior. These include annular centrifugal contactor, jet loop reactor, ultrasound reactor, channel flow, stirred tank and bubble column reactor. The characterization of their dynamics based on denoising the data and studying the local energy along the WT scales show sensitive variation and this helps in identifying the size and shape of structures. A dependency is seen between mixing time and the higher order moments of length scale distribution, viz., skewness and kurtosis and a generalized correlation has been built up for important types of equipment and associated flow parameters. The correlation is not only based on the knowledge of reactor geometry and operating conditions but also on the flow structures via their statistical parameters. Wavelet transform modulus maxima (WTMM) methodology has been used to study the evolution of structures and their interaction in a reduced dimensionality by evaluating the fractal spectra. Classification studies have been carried out using principal component analysis (PCA) of the fractal spectra. The results obtained show clear classes for the six types of equipments and delineate regimes to obtain benchmark patterns of flow hydrodynamics based on PCA co-ordinates. This methodology offers a generalized way for the optimal design and operation of different types of reactors. (c) 2008 Published by Elsevier Ltd .
Keywords: Chemical reactors; hydrodynamics; Length scale distribution; mixing; Model reduction; Turbulence; Wavelet transform

Development of correlations for overall gas hold-up, volumetric mass transfer coefficient, and effective interfacial area in bubble column reactors using hybrid genetic algorithm-support vector regression technique: viscous newtonian and non-newtonian liq - Gupta, Prashant P.; Merchant, Shamel S.; Bhat, Akshay U.; Gandhi, Ankit B.; Bhagwat, Sunil S.; Joshi, Jyeshtharaj B.; Jayaraman, Valadi K.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
The objective of this study was to develop hybrid genetic algorithm-support vector regression (GA-SVR)-based correlations for overall gas hold-up (epsilon(G)), volumetric mass-transfer coefficient (kt,a), and effective interfacial area (a) in bubble Column reactors for gas-liquid systems employing Viscous Newtonian and non-Newtonian systems as the liquid phase. The hybrid GA-SVR is a novel technique based on the feature 0 generation approach using genetic algorithm (GA). In the present study, GA has been used for nonlinear rescaling of attributes. These, exponentially scaled, are eventually subjected to SVR training The technique is an extension of conventional SVR technique, showing relatively enhanced results For this purpose an extensive literature search was done. From the published literature, 1629 data points for viscous Newtonian and 845 data points for VISCOUS non-Newtonian systems for cc;, 500 data points for viscous Newtonian and 556 data points for viscous non-Newtonian systems for k(L)a, and 208 data points for viscous non-Newtonian systems for a, respectively, were collected These data sets were collected spanning the years 1965-2007 Correlations were developed after taking into account all the parameters affecting epsilon(G), k(1)a, and a such as column and sparger geometry, gas-liquid properties, operating temperature, pressure, and Superficial gas and liquid velocities. The correlations thus developed gave prediction accuracies of 0.994 and 0.999 and average absolute relative errors (AARE) of 3.75 and 1.65% for viscous Newtonian and non-Newtonian systems for epsilon(G), prediction accuracies of 0.983 and 0.998 and AARE of 8 62 and 1.91% for viscous Newtonian and non-Newtonian systems for k(1)a, and prediction accuracy of 0.999 and AARE of 1% for viscous non-Newtonian systems for a, respectively. These correlations also showed much improved results when compared with all the existing correlations proposed in literature. To facilitate their usage, all the hybrid GA-SVR-based correlations have been uploaded on the web link http-//wwwesnips.com/web/UICT-NCL.

Development of unified correlations for volumetric mass-transfer coefficient and effective interfacial area in bubble column reactors for various gas-liquid systems using support vector regression - Gandhi, Ankit B.; Gupta, Prashant P.; Joshi, Jyeshtharaj B.; Jayaraman, Valadi K.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
The objective of this study was to develop a unified correlation for the volumetric mass-transfer coefficient (k(L)a) and effective interfacial area (a) in bubble columns for various gas-liquid systems using support vector regression (SVR-) based modeling technique. From the data published in the open literature, 1600 data points from 27 open sources spanning the years 1965-2007 for k(L)a and 1330 data points from 28 open sources spanning the years 1968-2007 for a were collected. Generalized SVR-based models were developed for the relationship between k(L)a (and a) and each design and operating parameters such as column and sparger geometry, gas-liquid physical properties, operating temperature, pressure, superficial gas velocity, and so on. Further, these models for k(L)a and a are available online at http://www.esnips.com/web/UICT-NCL. The proposed generalized SVR-based correlations for k(L)a and a have prediction accuracies of 99.08% and 98.6% and average absolute relative errors (AAREs) of 7.12% and 5.01%, respectively. Also, the SVR-based correlation provided much improved predictions compared to those obtained using empirical correlations from the literature.

Effect of flow structures on heat transfer in single and multiphase jet reactors - Deshpande, Sagar S.; Mathpati, Channamallikarjun S.; Gulawani, Sagar S.; Joshi, Jyeshtharaj B.; Kumar, V. Ravi (Industrial & Engineering Chemistry Research, 2009)
High frequency experimental measurements by hot film anemometry (HFA) of liquid velocities and temperature in the region of vapor-liquid (VL) and solid-liquid (SL) interfaces for two important reactor types, namely, condensation jet and jet loop reactors, have been studied for their heat transfer characteristics. An algorithm for flow structure identification has been devised from velocity data based oil (i) zero crossings and (ii) continuous wavelet transform. The wavelet transform algorithm is especially found to be useful in accurately estimating both the age and size distributions of eddies near interfaces in a multiscale framework Using these distributions, it is shown that the calculated values of heat transfer coefficients (HTC) at the SL and VL interfaces show remarkable correspondence with the HTC values obtained experimentally from instantaneous temperature measurements. For this purpose, a modified capacitance model has been proposed that takes into account the information about both the age and size distributions. The results obtained by the present methodology show the improvement possible for calculating the HTC at interfaces when compared with the earlier surface renewal models. It may therefore be used to study the interaction between flow dynamics and heat transfer behavior in chemical process equipment

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

Preparation of pure methyl esters from corresponding alkali metal salts of carboxylic acids using carbon dioxide and methanol - Barve, Prashant P.; Kamble, Sanjay P.; Joshi, Jyeshtharaj B.; Gupte, Milind Y.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
In the present article, for the first time, we report the synthesis of alkyl esters by direct esterification of alkali metal salts of carboxylic acids using carbon dioxide and alcohol. Methyl acetate, methyl benzoate, methyl salicylate, and methyl lactate have been synthesized by esterification of sodium acetate, sodium benzoate, sodium salicylate, and calcium lactate, respectively. The esterification reaction was carried out in a batch as well as in a semicontinuous mode of operation. A detailed study on the esterification of calcium lactate using methanol and carbon dioxide was carried out to record the effects of various operating parameters (like CO2 pressure, reaction temperature, moisture content in the calcium lactate, and initial concentrations of calcium lactate) on the esterification reaction. This synthesis route produces highly pure methyl lactate by direct esterification of calcium lactate with calcium carbonate as byproduct. The byproduct calcium carbonate was characterized for its crystallinity, surface area, and pore volume. The process route has the advantage that the synthesized byproduct can be recycled into the fermenter to make corresponding alkali metal lactate or the finely precipitated calcium carbonate can be used for various other applications. Thus, the recovery and recycle of alkali metal is possible providing a pollution free process for synthesis of pure methyl lactate.

Purification of lactic acid via esterification of lactic acid using a packed column, followed by hydrolysis of methyl lactate using three continuously stirred tank reactors (CSTRs) in series: a continuous pilot plant study - Kamble, Sanjay P.; Barve, Prashant P.; Joshi, Jyeshtharaj B.; Rahman, Imran; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
The world market of lactic acid is growing every year, mainly as a solvent and precursor to poly(lactic acid) (PLA). The cost of renewable biomass-derived PLA will have to compete with other synthetic polymers, if it is to grab a significant and sustainable fraction of the market share. It is thus necessary to have efficient and cost-effective technology for the production of pure-grade lactic acid (LA). In this article, a novel cost-effective, eco-friendly continuous process for the production of high-quality lactic acid at pilot plant scale has been demonstrated. The novelty of this process is that, for the first time, we report and use the concept of inverse reactive distillation for the esterification of crude concentrated LA in a continuous countercurrent packed column mode. This allows us to operate the column at higher temperatures, improving the kinetic rate process and leading to shorter columns. This is followed by the hydrolysis of methyl lactate (MLA) in a series of three continuously stirred tank reactors (CSTRs), where LA itself acts as a catalyst. The LA obtained in the pilot plant process shows 99.81% purity (by weight) on water-free basis and has an optical purity of 99.9%. The pilot scale experimental results pertaining to the autocatalytic esterification of LA and hydrolysis of MLA have been compared and validated, with respect to simulated results. The innovations reported here can make the process economically viable for commercial use.